2014
DOI: 10.3109/09638288.2014.964376
|View full text |Cite
|
Sign up to set email alerts
|

Development of a family-based pulmonary rehabilitation programme: an exploratory study

Abstract: PR programmes, if inclusive of family members, may enhance the skills of the whole family to manage COPD. Implications for Rehabilitation Patients with chronic obstructive pulmonary disease (COPD) and their family members have similar expectations and needs about a family-based pulmonary rehabilitation (PR) programme. A family-based PR programme is feasible to implement within primary care. PR programmes, if inclusive of family members, may enhance the skills of the whole family to manage COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(64 citation statements)
references
References 41 publications
1
63
0
Order By: Relevance
“… 43 No significant change was established after low-intensity training. 43 Four studies measured isotonic quadriceps strength via 10RM, with three studies showing a 63.4–96.9% increase in 10RM leg extension, 48 , 51 , 52 while another study reported a 71.0% increase in 10RM weightlifting after training. 53 A 15RM leg press was measured in one study, with a mean change of 16 kg reported after training, which was significantly different with controls whom did not show a significant change.…”
Section: Resultsmentioning
confidence: 99%
“… 43 No significant change was established after low-intensity training. 43 Four studies measured isotonic quadriceps strength via 10RM, with three studies showing a 63.4–96.9% increase in 10RM leg extension, 48 , 51 , 52 while another study reported a 71.0% increase in 10RM weightlifting after training. 53 A 15RM leg press was measured in one study, with a mean change of 16 kg reported after training, which was significantly different with controls whom did not show a significant change.…”
Section: Resultsmentioning
confidence: 99%
“…Our search identified 76 unique studies, of which 15 fulfilled eligibility criteria. 11,12,[18][19][20][21][22][23][24][25][26][27][28][29][30] Reasons for exclusion were no balance or fall risk outcome reported (n = 3), not describing original data (n = 1), results from patients with COPD were not specified (n = 2), not meeting the mini-mum intervention duration of 14 d (n = 1), and no RCT or a within-group study design (n = 1) (see Supplemental Digital Content 2, available at: http://links.lww.com/JCRP/ A174).…”
Section: Study Selectionmentioning
confidence: 99%
“…Other domains, assessed in the studies, comprised both the negative and positive aspects of caregiving (Caregiver Reaction Assessment [25,47,61,62]; Family Appraisal of Caregiving Questionnaire for Palliative Care [23,63]), disability due to the partner's disease (COPD Disability Index [50], which was a modified version of the Pain Disability Index), objective and subjective health status (Health Perceptions Questionnaire Form II e only the Current Health subscale was used [48]), low back pain prevalence and impact (Nordic low back pain questionnaire [60]), psychosocial impact of the illness (Psychosocial Adjustment to Illness Scale e Self-Report [32,33]), loneliness (revised UCLA Loneliness scale [43,64]), spiritual wellbeing (Functional Assessment of Chronic Illness Therapy 12-item Spiritual Well-Being Scale [47]) and life satisfaction (Life Satisfaction Index-A [65]).…”
Section: Instrumentsmentioning
confidence: 99%